The Influence of Reward and Punishment on Employee Performance at Komodo Labuan Bajo Airport. - Maria Komang Devi Bengan Demon; Arif Fakhrudin (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Komodo Labuan Bajo Airport is one of the airports located in East Nusa Tenggara. In addition to the importance of airport development, human resources are also one of the assets that the company pays close attention to. Human resources are a supporting factor for the success of a business sector. Because employees are a very important asset for airport provider companies, companies must pay attention to the obligations that employees deserve, namely rewards and punishments as an effort to be able to create optimal and satisfying employee performance. This research was conducted to find out whether there is an effect of reward and punishment on the performance of Komodo Labuan Bajo airport employees. This research was processed using quantitative research methods, with a research instrument, namely a questionnaire. The results of the study show that: 1) Reward has a partial effect on the performance of Komodo Labuan Bajo airport employees. 2) Punishment has a partial effect on the performance of Komodo Labuan Bajo airport employees. 3) Reward and punishment have a simultaneous effect on the performance of Komodo Labuan Bajo airport employees. 4) Rewards have a more dominant effect on the performance of Komodo Labuan Bajo airport employees.